2020
DOI: 10.1016/j.heliyon.2020.e04188
|View full text |Cite
|
Sign up to set email alerts
|

Lead tolerant endophyte Trametes hirsuta improved the growth and lead accumulation in the vegetative parts of Triticum aestivum L.

Abstract: Rapid industrialization and increasing population are continuously adding contaminants to our environment. Among those, heavy metals are considered to be one of the serious threats to the ecosystem due to their persistent nature. Microbe assisted phytoremediation is an effective tool for metal remediation as microbes enhance the metal availability and uptake to the host plants or reduce it by binding them intracellularly or extracellularly. An endophytic fungus, Trametes hirsuta , was is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Endophytes have stood out for their ability to synthesize and accumulate secondary metabolites in the tissues of their hosts which can influence the functioning of antioxidant enzymes, in turn activating the cascade of defense signals and promoting the positive regulation of gene expression of important enzymes during the production of secondary metabolites [ 221 ]. In this sense, several studies have shown that the association of endophytes increases tolerance to abiotic stresses [ 221 , 222 , 223 , 224 , 225 , 226 ].…”
Section: Endophytes In Inducing Tolerance To Abiotic Stressesmentioning
confidence: 99%
See 2 more Smart Citations
“…Endophytes have stood out for their ability to synthesize and accumulate secondary metabolites in the tissues of their hosts which can influence the functioning of antioxidant enzymes, in turn activating the cascade of defense signals and promoting the positive regulation of gene expression of important enzymes during the production of secondary metabolites [ 221 ]. In this sense, several studies have shown that the association of endophytes increases tolerance to abiotic stresses [ 221 , 222 , 223 , 224 , 225 , 226 ].…”
Section: Endophytes In Inducing Tolerance To Abiotic Stressesmentioning
confidence: 99%
“…The role of endophytes in providing tolerance to heavy metal stresses has been observed in plant cultures such as Triticum aestivum [ 224 , 240 ], Lycopersicon esculentum [ 241 ], and Glycine max [ 242 ], among others. For example, the endophytic P. roqueforti fungus induced resistance in T. aestivum plants grown in soil contaminated with heavy metals, restricting heavy metal transfer from the soil to the plants, and secreting indole acetic acid.…”
Section: Endophytes In Inducing Tolerance To Abiotic Stressesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, in vitro bioremediation potential of endophytic fungal consortium isolated from Agrostis stolonifera in lead-contaminated soil has been reported to stimulate the growth of test plant Festuca arundinacea Schreb under heavy metal toxicity ( Soldi et al, 2020 ). Similarly, endophytic fungus, Trametes hirsuta , isolated from lead-stressed Chenopodium album L. plant has been documented to provide lead tolerance to Triticum aestivum L. seedlings and thus resulted in endophyte-assisted phytoremediation ( Malik et al, 2020 ). The recent functional role of mercury-resistant endophytic fungal strains ( Aspergillus sp.…”
Section: Applications Of Endophytic Fungi As Biocatalystmentioning
confidence: 99%
“…tritici , and F. culmorum . Meanwhile, Malik et al [ 163 ] showed that inoculation with endophytic fungus Trametes hirsuta , isolated from the Chenopodium album L. plant, may improve the survival of wheat plants in metal-contaminated soils and may additionally assist in the phytoextraction of heavy metals (Pb). Similar properties in relation to wheat plant were revealed for P. ruqueforti isolated from the endosphere of Solanum surattense [ 164 ].…”
Section: Application Of Endophytic Fungi In Modern Agronomymentioning
confidence: 99%